Different nucleos(t)ide analogs in resected hepatitis B virus-associated hepatocellular carcinoma: a systematic review - Qiu, Hongquan; Zhang, Yu; Xu, Fengxia; Xue, Songhui (Frontiers in Pharmacology, 2025)
BackgroundTo evaluate the effects of different types of nucleos(t)ide analogs on the survival rate of patients with hepatitis B virus-associated hepatocellular carcinoma (HBV-HCC) after radical resection through a network meta-analysis.MethodsPubMed, Embase, the Cochrane Library, and CNKI databases were searched up to 6 March 2024. The NOS was used to assess the risk of bias in cohort studies, while the ROB tool in Review Manager was employed for randomized controlled trials. Data on overall survival (OS) and recurrence-free survival (RFS) were extracted from the literature to pool hazard ratios (HRs) and corresponding 95% CrIs. Meta-analysis was performed via R.Results24 studies involving 9,787 HBV-HCC patients were included. Compared with the control group, antiviral therapies using telbivudine (HR [95% CrI] = 0.23 [0.12,0.44]), tenofovir disoproxil fumarate (HR [95% CrI] = 0.40 [0.30,0.52]), lamivudine (HR [95% CrI] = 0.50 [0.34, 0.75]), adefovir (HR [95% CrI] = 0.55 [0.38,0.79]), and entecavir (HR [95% CrI] = 0.55 [0.43,0.71]) significantly improved OS. Among these, telbivudine (98.22%) and tenofovir disoproxil fumarate (76.12%) demonstrated superior effects in improving OS. Compared with the control group, antiviral therapies using telbivudine (HR [95% CrI] = 0.45 [0.28,0.70]), tenofovir disoproxil fumarate (HR [95% CrI] = 0.52 [0.44,0.62]), entecavir (HR [95% CrI] = 0.65 [0.55,0.77]),adefovir (HR [95% CrI] = 0.79 [0.65,0.94]),and lamivudine (HR [95% CrI] = 0.82 [0.71, 0.94]) significantly improved RFS. Telbivudine (SUCRA, 93.22%) and tenofovir disoproxil fumarate (SUCRA, 85.37%) exhibited superior effects in improving RFS.ConclusionWhen compared to other nucleos(t)ide analogs, telbivudine and tenofovir disoproxil fumarate exhibited the most notable effects.Systematic ReviewIdentifier CRD42024612794.